2022
DOI: 10.1186/s12936-022-04141-6
|View full text |Cite
|
Sign up to set email alerts
|

Changing transmission dynamics among migrant, indigenous and mining populations in a malaria hotspot in Northern Brazil: 2016 to 2020

Abstract: Background Roraima state is the northernmost state in Brazil and the primary border-crossing point between Brazil and Venezuela. The uncontrolled surge of malaria in Venezuela, coupled with mass migration of Venezuelans to neighbouring countries and the upward trend in informal mining in the state, pose a serious threat to the broader region, especially to migrant, indigenous and mining populations, jeopardizing malaria elimination efforts. This study describes changes in the epidemiological pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Combined with setbacks, the rise in the gold price in recent years has increased pressure on these protected areas; in the 2019–2021 period, the gold price increased more than 30%, reaching up to $65 g −1 , the highest value of the last ten years ( https://goldprice.org ). In addition to the environmental impact, the anthropic advance on indigenous territories also serves as a vector of diseases, such as malaria, associated with illegal mining activities, which may decimate indigenous peoples along with their culture and knowledge 45 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Combined with setbacks, the rise in the gold price in recent years has increased pressure on these protected areas; in the 2019–2021 period, the gold price increased more than 30%, reaching up to $65 g −1 , the highest value of the last ten years ( https://goldprice.org ). In addition to the environmental impact, the anthropic advance on indigenous territories also serves as a vector of diseases, such as malaria, associated with illegal mining activities, which may decimate indigenous peoples along with their culture and knowledge 45 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Combined with setbacks, the rise in the gold price in recent years has increased pressure on these protected areas; in the 2019-2021 period, the gold price increased more than 30%, reaching up to $65 g -1 , the highest value of the last ten years ( https://goldprice.org ). In addition to the environmental impact, the anthropic advance on indigenous territories also serves as a vector of diseases, such as malaria, which is associated with illegal mining activities, may decimate indigenous peoples along with their culture and knowledge [33][34][35] .…”
Section: Resultsmentioning
confidence: 99%
“…8 Nevertheless, the favorable environment for Anopheles species mosquitoes reproduction and dissemination in water reservoirs left in the mines increases the risk of infection among miners. 4…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that the loss of forest cover is a significant predictor of malaria transmission in the Amazon region, with a higher prevalence of the disease among Yanomami indigenous children and adolescents. 4 In this study, we investigate the incidence of malaria among Yanomami indigenous children and adolescents residing in the Brazilian Legal Amazonia territory.…”
mentioning
confidence: 99%